The effect of gamma-irradiation on morphology and properties of melt-spun poly (lactic acid)/cellulose fibers. (February 2019) - Aouat, Tassadit; Kaci, Mustapha; Lopez-Cuesta, José-Marie; Devaux, Eric; Mahlous, Mohamed
Abstract: The effect of gamma irradiation on both morphology and properties of neat poly(lactic acid) (PLA), PLA/microcrystalline cellulose (MCC) and PLA/cellulose nanowhiskers (CNW) fibers loaded at 1 wt% filler content was investigated in presence of PLA-grafted maleic anhydride (PLA -g- MA) used as the compatibilizer. Multifilament yarns were prepared by a melt-spinning process and subjected to gamma irradiation at various doses from 5 to 30 kGy keeping the dose rate at 1.92 kGy/h under ambient conditions. Chemical structure, morphology and property changes induced by gamma irradiation on the samples were evaluated by several techniques considering the filler aspect ratio effect. The results showed a dose-related increase in the scission index (SI) of the irradiated samples whatever the filler size, while thermal and tensile properties significantly decreased. However, the incorporation of cellulosic fillers in PLA fibers, in particular MCC, was found to hinder the radiolytic degradation process of the irradiated samples. Highlights: Gamma radiation-induced degradation of Poly(lactic acid)/Cellulose fibers. PLA fibers undergo degradation due to chain scission mechanism. Neat PLA is more sensitive to ɣ-irradiation than the nanobiocomposite fibers. The degradation process of PLA is slower in presence of MCC compared to CNW.